Dampak Negatif Gadget pada Perilaku Agresif Anak Usia Dini - Anwardiani Iftaqul Janah; Raden Diana (UIR PRESS, 2023)
Technology that is currently developing has an influence on aggressive behavior in children, so there needs to be prevention efforts in this deviant behavior. The purpose of this study was to determine the influence of gadgets and the factors that cause aggressive behavior, forms of aggressive behavior, the impact of aggressive behavior, and efforts to handle aggressive behavior in early childhood. The method used in this research is a case study which is presented with a qualitative descriptive research type by presenting the data in a narrative manner, as well as data obtained through observation. In this study, the subject is one girl who behaves aggressively aged 5-6 years because of the influence of unlimited gadgets. The results of the research obtained are the influence of the use of gadgets that are not restricted and supervised. This causes aggressive behavior in children who find it difficult to control their desire to convey messages, such as shouting, crying, and making physical contact when someone interferes with playing gadgets. The influence of gadgets on aggressive behavior in children requires serious efforts for parents or adults who are around children so that they do not have a negative impact on children's development in the future.